MENGENAL KETOKOHAN QURAISH SHIHAB SEBAGAI PAKAR TAFSIR INDONESIA - Kumalasari, Reni (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2021)
Quraish Shihab is not the only expert on the interpretation of the Qur'an in Indonesia, but his ability to translate and convey the messages of the Qur'an in the present and modern context makes him superior to other Qur'anic experts. His works on the Qur'an can easily be accepted not only academics, but the general public. This study aims to examine the thoughts of Quraish Shihab in the field of tafsir in general by using a literature review approach. The results showed that Quraish Shihab was a competent commentator in the archipelago. He tries to touch the Qur'an with the reality of modern human life today which is called with the term grounding the Qur'an. In terms of method, he tends to use thematic interpretation because it is more appropriate to reveal the content of the Qur'an on various problems of Muslims today.